Good practices in delivery and birth care: perceptions of Primary Care nurses - Luana Fietz da Silva Raznievski; Fernanda Almeida Fettermann; Andriele Berger da Rosa; Juliana Silveira Bordignon; Hilda Maria Barbosa de Freitas; Daiany saldanha da silveira Donaduzzi (Universidade Federal de Santa Maria, 2020)
Objective: to identify the perceptions of Primary Care nurses about good practices in delivery and birth care from the perspective of the Evidence-Based Practices. Method: a descriptive, exploratory, and qualitative study, conducted in April and May 2018 with 20 nurses from a city located in the central region of the state of Rio Grande do Sul, Brazil. Semi-structured interviews and a questionnaire to collect sociodemographic data and Content Analysis were used. Results: the nurses perceive prenatal care as a time to guide pregnant women so that they have autonomy and empowerment; however, the professionals did not receive qualifications for guidelines related to good practices in delivery and birth care. Conclusion: the nurses' work process must be supported by permanent education that considers the care practice supported by scientific evidence.